Russian authority and the Internet: safety vs freedom of speech - I. A. Lavrov; A. V. Sokol (Цифровая социология)
The Internet, in the era of its availability and popularity in modern Russia, plays the most important role both in the dissemination of information and in the daily communications of people. Mass media also use Internet platforms as the main ones in their activities, because traditional forms of media already have a smaller audience coverage, than online-editions. Due to the fact, that in the modern Russia traditional mass media are controlled by the authorities, the Internet remains the last platform, on which independent sources can lead their activities. For today, Internet is the main force, shaping public opinion and trends. In this regard, the current Russian government has a need to develop new measures and introduce new laws to regulate this area. But is it really the primary authority`s task to ensure security within the Russian Internet, or is it driven by the desire to take control of the Internet and restrict its freedom?The main actions of the Russian authorities, taken to ensure the security of the Russian Internet, in chronological order, have been considered and analyzed. Both texts of laws and their real results after adoption have been reviewed and analyzed. For each such action an assessment of public opinion in relation to these innovations has been adduced. The compliance of the stated goals and objectives of the draft laws with their actual results has been considered. The analysis of international assessments of freedom of the mass media, freedom of the Internet and individual freedom in the Russian Federation during various periods of the implementation of these laws in everyday life has been given.